Molecular mapping of quantitative trait loci (QTL) for Fusarium head blight (FHB) resistance and agronomic traits in US hard winter wheat - Xu, Yuzhou (Kansas State University, 2023)
Fusarium head blight (FHB) is one of the devastating fungal diseases in wheat and results in dramatic losses in grain yield and quality. Use of genetic resistance is an effective approach to FHB control, but highly FHB resistant germplasms usually have many undesirable agronomic traits. To dissect the relationship between FHB resistance and yield component traits, we developed two recombinant inbred line (RIL) populations for identification of native FHB resistance quantitative trait loci (QTL) in US hard winter wheat by genotyping the populations with single nucleotide polymorphism (SNP) markers generated from genotyping-by-sequencing (GBS) and phenotyping the FHB and agronomic traits in both greenhouse and field experiments. In the G97252W x G97380A RIL population, one major native QTL (QFhb.hwwg-2DS) was mapped on chromosome arm 2DS for FHB resistance even after removing the confounding effects from heading date (HD) and plant height (HT). QFhb.hwwg-2DS coincided with the major QTL for HT, HD, spike length (SL), kernel number per spike (KNS), spikelet number per spike (SNS), thousand grain weight (TGW), and grain size. Additional QTL for spike and grain traits were identified on chromosome arms 2AL, 2DS, 3AL and 4BS. G97252W contributed FHB resistance and high SNS alleles at QFhb.hwwg-2DS, as well as high KNS alleles at the QTL on 2AL and 2DS, and high TGW and large grain size alleles at the QTL on 3AL, whereas G97380A contributed high TGW and large grain size alleles at the QTL on 2AL and 2DS, respectively, and the high KNS allele at the 4BS QTL. In the JagR1097 x Jagger RIL population, three QTL for FHB resistance were detected on chromosome arms 4AL, 4DL and 6AL, even after removing the effects from HD and HT. QFhb-4AL from Jagger showed a major effect that had 11.80% of the phenotypic variation for FHB resistance and was coincided with the major QTL for HT, HD, SL and SNS. QTL clusters were identified on chromosome arms 2BS, 2DL, 3AS, 3DL, 4BS, 5AS, 5DL and 7AL for different agronomic traits. Jagger contributed FHB resistance and high SNS alleles at QFhb-4AL as well as high SNS alleles at the QTL on 5DL. whereas JagR1097 contributed FHB resistance alleles at the QTL on 4DL and 6AL, and high TGW alleles at the QTL on 3AS and 4BS, and the high SNS allele at the QTL on 2BS and 7AL. Pyramiding those FHB resistance QTL with positive alleles for spike and grain traits from different chromosomes may simultaneously improve FHB resistance and grain yield in new cultivars.
Keywords: Wheat; Fusarium head blight; Fusarium head blight resistance; Developmental and yield traits; Pleiotropic quantitative trait locus